2000
DOI: 10.1177/000313480006600615
|View full text |Cite
|
Sign up to set email alerts
|

Do Patients with Acute Deep Vein Thrombosis Have Fever?

Abstract: The purpose of this study was to determine whether those with lower extremity acute venous thrombosis have fever. During a recent 14.5-month period, 1847 patients undergoing lower extremity venous duplex scanning also had their oral temperature measured using a digital thermometer at the time of duplex examination. Patients were 57.8 ± 17.3 years of age (range, 14 to 99). Temperature was 98.5 ± 1.1° F. Twenty-three patients had acute inferior vena cava thrombosis, 60 had acute iliac vein thrombosis, 138 had ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 10 publications
(1 reference statement)
0
9
0
Order By: Relevance
“…Although the study by Kazmers et al did not demonstrate that fever is a strong indicator of DVT, the more recent study by Barba et al showed worse outcomes for patients experiencing both fever and DVT and provides a sufficient reason to diagnose DVT in a febrile patient as soon as possible so that appropriate treatment can be started. 2,12 This combined research demonstrates that the presence of fever alone can be an indication of existing DVT and warrants an ultrasound examination. While the wish to preserve a sonographer's time to perform this examination when it is truly needed, the data collected show that there is a correlation between DVT and FUO and that, when coexisting, they pose a dangerous threat to the patient's wellbeing.…”
Section: Deep Venous Thrombosis In the Setting Of Fevermentioning
confidence: 84%
See 4 more Smart Citations
“…Although the study by Kazmers et al did not demonstrate that fever is a strong indicator of DVT, the more recent study by Barba et al showed worse outcomes for patients experiencing both fever and DVT and provides a sufficient reason to diagnose DVT in a febrile patient as soon as possible so that appropriate treatment can be started. 2,12 This combined research demonstrates that the presence of fever alone can be an indication of existing DVT and warrants an ultrasound examination. While the wish to preserve a sonographer's time to perform this examination when it is truly needed, the data collected show that there is a correlation between DVT and FUO and that, when coexisting, they pose a dangerous threat to the patient's wellbeing.…”
Section: Deep Venous Thrombosis In the Setting Of Fevermentioning
confidence: 84%
“…The objective of the study by AbuRahma et al was to see whether the presence of DVT could explain a patient's FUO, whereas Kazmers et al sought to document how many times DVT and fever coexisted to provide more clarity on the clinical correlation, if any. 10,12 A more recent study published by Barba et al 2 in 2011 states that the presence of fever can be a warning sign of acute DVT. This study is different than the 2 previously discussed studies because its objective is not to provide data supporting a connection between the 2 variables.…”
Section: Deep Venous Thrombosis In the Setting Of Fevermentioning
confidence: 99%
See 3 more Smart Citations